Scientific and Technical Challenges in Electricity Generation - Harold M. Hubbard (CHIMIA)
Three renewable energy technologies for power systems - photovoltaics, wind, and solar thermal - are discussed. Based on world-wide experience with these systems, methods of improving efficiency, reliability, and cost for commercial electricity generation are described.